STUDY OF THE PHYSOCHEMICAL, RHEOLOGICAL AND SENSORY PROPERTIES OF YOGHURT FORTIFIED WITH MICROENCAPSULATION IRON - & Doosh, Sadiq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to determine the effect of milk fortification with encapsulated and non-encapsulated iron on the physiochemical, rheological and sensory properties of the functional yoghurt. Different concentrations of capsulated ferrous sulphate 5, 7.5, 15 mg / 100ml milk were used and represented as T2,T3 and T4 treatments respectively, as well as the treatment with non-encapsulated iron 15 mg / 100 ml as T1 and control treatment (C) in which yoghurt was made from whole milk without iron addition. The physiochemical, rheological and sensory properties of the products were tested during storage period at a temperature ( 5 ± 1) ° C. The results revealed that there was no significant differences (p<0.05) between control and other treatments in moisture, protein, fat carbohydrate, ash content. In addition, the fortified yoghurt samples were showed low ADV and PV values and better sensory and rheological properties.